Polydactyly 24 in a Female Neonate. (5th September 2013) - Atanda, Oluseyi O. A.; Owonikoko, Kola M.; Adeyemi, Adewale S.; Bajowa, Olanrewaju
Abstract : Polydactyly is perhaps one of the most common congenital hand and foot anomalies. Tetrapolydactyly (polydactyly 24) is a very rare form of hand and foot anomalies. Postaxial ray polydactyly usually occurs in male blacks without associated congenital abnormalities. We report a case of postaxial ray tetrapolydactyly in a female neonate which occurred sporadically and without associated congenital abnormalities.